Review of the effects of manufactured nanoparticles on mammalian target organs. Issue 1 (11th August 2017) - Wu, Tianshu; Tang, Meng
Abstract: Nanotechnology had matured significantly during the last two decades as it has transitioned from bench top science to applied technology. Even though the issue of safety of nanotechnology has been raised nearly one decade ago, the rapid progress in development and use of nanomaterials has not yet been matched by toxicological investigations. Many recent studies have simply outlined the toxic effects of nanoparticles (NPs), but few have systematically addressed their potentially adverse biological effects on target organs. Some animal models have shown that NPs could be accumulated in various organs. These accumulations can access the vasculature and target other organs, resulting in a potential health risks. After the brief description of current knowledge on the wide applications of several common NPs, their applications and the toxicokinetics, this review focused on effects of NPs on organ functions and mammal health after acute or chronic exposure, and potential mechanisms of action. Due to their physical properties, the liver, kidneys and lung are the main target organs of NPs. Most of NPs show slight toxicity when exposed to animals, while certain toxic effects like oxidative stress generation, inflammation and DNA damage are commonly observed. The severity of NPs toxicity is dependent upon several factors, including exposure dose and administration, NPs chemistry, size, shape, agglomeration state, and electromagnetic properties, which could provide useful information necessary to control the toxicity of NPs. Finally, the safety evaluation of nanotoxicity was addressed. Abstract : It is important to systematically address the potential adverse biological effects of NPs on target organs. This review focused on the effects of NPs on main target organs, like liver, kidneys and lung, and adverse effects include organ dysfunctions, oxidative stress damage, inflammation and DNA damage. The severity of NPs toxicity is dependent on several factors.